AN INDIVIDUAL PSYCHOLOGY PERSPECTIVE ON IAN’S EFFORT TO OVERCOME INFERIORITY IN ONWARD 2020 - Ayub, Sahid Hasanudin; Wulandari, Diyah Fitri (Jurnal Ilmiah Penelitian Mahasiswa, 2025)
Teenagers commonly experience feelings of inferiority as part of their growth and maturation. The film Onward portrayed this through its main character, Ian Lightfoot, who also struggled with such feelings. In this qualitative study, the discussion centers on the essential principles of Alfred Adler's individual psychology theory, namely fictional finalism, style of life, creative self, striving for superiority, and social interest. Additionally, this study explained various forms of compensation Ian demonstrated in dealing with his inferiority, including stubbornness, rebelliousness, disrespect, courage, a challenging attitude, confidence, and collaboration. Understanding these aspects is important to show how feelings of inferiority could positively contribute to psychological growth through appropriate compensatory mechanisms.Kata Kunci: Teenagers, Inferiority feeling, Onward, Ian Lightfoot